Решите расскрыв скобки (+7)-(-4)+(-14)= (-5)-(-15)-(+8)= (+3)+(-10)-(+6)-(-7)= (+6)-(+9)+(-2)-(-4)-(+11)= (-8)-(+1)-(-14)-0+(-7) (+24)+(-2)-(-3)-(+24)+(-5)= (-4)-(+7)+(-16)-(-16)-(+1)-(-4)= (+2)-(-5)+(-12)-(+2)-(-12)+(+5)= (-9)...

Решите расскрыв скобки (+7)-(-4)+(-14)= (-5)-(-15)-(+8)= (+3)+(-10)-(+6)-(-7)= (+6)-(+9)+(-2)-(-4)-(+11)= (-8)-(+1)-(-14)-0+(-7) (+24)+(-2)-(-3)-(+24)+(-5)= (-4)-(+7)+(-16)-(-16)-(+1)-(-4)= (+2)-(-5)+(-12)-(+2)-(-12)+(+5)= (-9)+(+1)-(+18)-(-9)+(-1)+(-18)= Зарание большое спасибо!!
Гость
Ответ(ы) на вопрос:
Гость
7+4-14=-3 -5+15-8=2 3-10-6+7=-6 6-9-2+4-11=-12 -8-1+14-0-7=-2 24-2+3-24-5=-4 -4-7-16+16-1+4=-8 2+5-12-2+12+6=11 -9+1-18+9-1-18=-36 Вроде правильно
Не нашли ответ?
Ответить на вопрос
Похожие вопросы